2019
DOI: 10.1159/000501710
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prepregnancy Body Mass Index, Weight Gain, and Gestational Diabetes Mellitus on Pregnancy Outcomes: A Population-Based Study in Xiamen, China, 2011–2018

Abstract: Background: It is unclear that how prepregnancy body mass index (BMI), gestational weight gain (GWG), and gestational diabetes mellitus (GDM) affect pregnancy outcomes in ­China. Thus, we explored how BMI, GWG, and GDM affect the risks of adverse pregnancy outcomes. Methods: We performed a retrospective, population-based study included all births in Xiamen, China, 2011–2018. Demographic data and pregnancy outcomes of 73,498 women were acquired from the Medical Birth Registry of Xiamen. Women were categorized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 0 publications
7
24
0
2
Order By: Relevance
“…However, we did not nd a signi cant relationship between obesity and macrosomia, consistent with a previous retrospective study found that high BMI had no signi cant impact on the risk of delivering LGA newborn or macrosomia, in PCOS women who underwent frozen embryo transfer (17). A study on general pregnant Chinese women found that overweight and obese women were more prone to have LGA and macrosomia compared to normal weight counterparts (18). A possible explanation for this phenomenon may be that different ways of conception have certain effects on pregnancy outcomes.…”
Section: Discussionsupporting
confidence: 89%
“…However, we did not nd a signi cant relationship between obesity and macrosomia, consistent with a previous retrospective study found that high BMI had no signi cant impact on the risk of delivering LGA newborn or macrosomia, in PCOS women who underwent frozen embryo transfer (17). A study on general pregnant Chinese women found that overweight and obese women were more prone to have LGA and macrosomia compared to normal weight counterparts (18). A possible explanation for this phenomenon may be that different ways of conception have certain effects on pregnancy outcomes.…”
Section: Discussionsupporting
confidence: 89%
“…However, there was no signi cant relationship between obesity and macrosomia, consistent with a previous retrospective study, which indicated that high BMI had no signi cant impact on the risk of delivering LGA newborn or macrosomia, in PCOS women who underwent frozen embryo transfer (19). A study involving general pregnant Chinese women found that overweight and obese women were more prone to have LGA and macrosomia compared with normal weight counterparts (20). A retrospective study involving 7122 general pregnant women from Bratislava, Slovakia, revealed that women with overweight and obesity had a 1.7-1.8 fold risk of macrosomia compared with normal weight women (21), but the study did not examine the correlation between BMI and LGA birth.…”
Section: Discussionsupporting
confidence: 87%
“…A total of 95.9% studies were prospective or retrospective cohorts and 4% were cross-sectional studies [20,21]. In addition, 17 (34.6%) studies used the GDM classification of group 1 [21,22,26,35,38,40,47,48,50,51,53,54,[59][60][61]64,67] and IADPSG; 7 (14.2%) group 2 [20,27,28,51,59,65,68], 3 (6.1%) group 3 [32,46,56], 1 (2%) group 4 [51], 19 (38.7%) group 5 [23][24][25]29,31,33,34,36,39,40,42,44,47,53,55,57,58,64,66], 6 (12.2%) group 6…”
Section: Discussionmentioning
confidence: 99%